(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
The forts are circular drystone structures. A description of the sites in the area is accompanied by plans of the surviving remains. The excavation of the fort at Borenich aimed to determine the nature of the structure, the quality of the masonry, whether it possessed chambers, the type of door or doors and to recover datable artefacts. The entrance passage was in two sections, the outer narrow, the inner wider, the division being caused by two door checks, one at each side. The checks consisted of fairly heavy flat stones bxiilt in at right angles to the line of the passage. The wall was ten feet in thickness and of basic construction and there was no evidence of chambers. Three fireplaces were identified. Artefacts included a quern, unidentified iron objects, a bone pin and a spindle whorl.